Pertimbangan Hakim Yang Memutus Persidangan In Absentia Dalam Kejahatan Desersi - Dava Prawira Wibowo (Faculty of Law, Universitas Lampung, 2023)
Military Members are limited by Laws and Military regulations so all the actions that are undertaken must also be based on Applicable laws and regulations. One of the most common crimes committed within the TNI is a criminal act of desertion desertion is the most prominent crime and must be done immediately resolved because it involves the integrity of the troop, it is necessary to regulate it specifically in order to be immediately decided and obtain legal certainty. However what if the military personnel who committed the crime of desertion could not found its existence or in this case the examination of the criminal act of desertion in absentia The method used by using a normative juridical approach method and supported by empirical juridical approach in the form of support from criminal law experts and law enforcement to support normative juridical data. Approach Normative juridical is done by seeing, analyzing and interpreting matters of a theoretical nature concerning legal principles through search related literature directly or indirectly direct Based on the results of research and discussion can be drawn a conclusion of the process the implementation of the desertion crime trial can be stated in absentia,if at the time of the third summons, the defendant still did not appear at the hearing (Law No. 31 of 1997 concerning Military Justice, Article 143). The judge's considerations in deciding the crime of desertion to three considerations, namely based on juridical considerations on formal statutory provisions, sociological considerations based on the social background of the defendant and for expediency, as well philosophical considerations with the aim that the sentence imposed against the accused as an effort to uphold discipline for each military member.